Czech Republic : Accounting and Auditing - World Bank (Washington, DC, 2013)
Financial reporting and auditing requirements in the Czech Republic are currently in transition from complying with national standards to complying with International Accounting Standards (IAS), International Standards on Auditing (ISA), and the European Union (EU) Directives. By law, the Czech Republic seeks to attain maximum compliance with the EU Fourth and Seventh Directives and the EU Regulation on the use of IAS, and to create an environment for implementing IAS for the financial statements of public interest entities by 2005. Small- and medium-size enterprises prepare their financial statements in accord with Czech Accounting Standards, which are largely based on the EU Directives and IAS. In practice, compliance with certain complex EU Directives and IAS requirements, including those dealing with consolidation and deferred tax, has been delayed. Presently, compliance with IAS is not effectively enforced. The transition to full IAS compliance for public interest entities will require extensive education in a different style and philosophy of accounting requirements. The transition to full IAS will require a culture shift to reduce the influence of tax accounting on general-purpose financial statements. By law, the Czech Republic seeks to comply with the EU Eighth Directive and ISA. There are, however, serious issues because Czech Standards on Auditing remain less robust than ISA, the Chamber of Auditors in the Czech Republic (CACR) has not adopted the International Federation of Accountants Code of Ethics, and certain EU Recommendations on auditor's independence and quality assurance have not yet been endorsed. While the Chamber of Auditors is aware of the challenges it faces, the transition to full ISA audits requires extensive education and strict enforcement of standards. This report draws upon recent international experience in developed economies and accession countries, as well as expected amendments to EU Directives, and recommends that the current self-regulation of the audit profession be reviewed and an adequate oversight mechanism established.